1996
DOI: 10.1590/s0004-282x1996000300002
|View full text |Cite
|
Sign up to set email alerts
|

Evolutional neurologic evaluation of seven year-old children born prematurely

Abstract: -A sample of 51 children aged 7 with a history of prematurity was compared to 44 age-matched children who were born at term at the HCPA. The premature children had had gestational ages up to 37 weeks and 6 days and were born weighing less than 2500g. The control group consisted of children born with gestational age between 38 and 42 weeks and weights above 2S00g. The evaluation criteria were clinical examination, neurological examination and the evolutional neurological evaluation (ENE). The results pointed ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…However, in this study, among patients with NE, 41 out of 544 (7.5%) were born prematurely, and 77 (14.2%) of 544 were born with a low BW. These demographic data show similar prevalence rates to those previously reported . Taken together, it can be considered to show a general tendency in the proportion of enuresis patients who were born prematurely.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, in this study, among patients with NE, 41 out of 544 (7.5%) were born prematurely, and 77 (14.2%) of 544 were born with a low BW. These demographic data show similar prevalence rates to those previously reported . Taken together, it can be considered to show a general tendency in the proportion of enuresis patients who were born prematurely.…”
Section: Discussionsupporting
confidence: 89%
“…Even decades ago, although premature birth was never specifically considered as the primary cause of NE, several studies have reported the association between BW and NE recently . A retrospective cohort study conducted in the United States showed that a low BW carries an increased risk of prolonged bedwetting .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolutional neurological evaluation (ENE) at 7 years of age in a group of preterms showed a statistically significant alteration in trunk-limb coordination in relation to term children 10 ; other studies assessing school-age children born at term have also observed unaltered trunk-limb coordination 11,12 . Our work aimed at verifying whether alterations in trunk-limb coordination can be observed in the 1st year of life in preterm children.…”
mentioning
confidence: 95%